Balancing Food Production and Biodiversity Conservation in Arable Landscapes: Lessons from the Farm4Bio Experiment. (1st August 2014) - Storkey, Jonathan; Holland, John; Henderson, Ian; Lutman, Peter; Orson, Jim; Baverstock, Jason; Pell, Judith
The success of crop protection products in reducing the impact of pests, weeds and diseases, along with increasing fertiliser use and a reduction in the diversity of crops being grown has led to undesired negative consequences for farmland biodiversity. The specific drivers of these declines in farmland wildlife have been extensively studied, especially for birds, leading to a number of high profile papers and the development of Entry Level and Higher Level Agri-environment schemes. However, while the farmland bird conservation agenda was a strong driver of agricultural land use policy in the late 1990s to mid 2000s, the more recent shift in emphasis towards increased food production and food security has brought into sharper relief the conflict between managing land for biodiversity and food. Faced with the pressures of an increasing population and climate change, there is a danger that non-crop biodiversity is seen as a luxury we may not be able to afford. In response to this increasing pressure on agricultural land and the drive towards so-called 'sustainable intensification', the production vs. conservation debate has shifted towards more fundamental questions. Firstly, can we define the relationships between the abundance of non-crop biodiversity and the ecosystem services they deliver that underpin crop production, including pollination and pest regulation? Secondly, how effective are current schemes in providing those services. Finally, how can biodiversity be integrated more efficiently into the landscape such that the minimum amount of land is lost to production. In 2006, the Farm4Bio project was set up as part of the Defra Sustainable Arable LINK programme to provide data to help answer these questions for arable landscapes in the UK.